Artificial Intelligence, its regulation in scientific research, the case of Mexico - Velazquez-Ramos, Cinthia Yareli (2026)
Generative Artificial Intelligence (GenAI) has increasingly been integrated into various stages of the scientific research process, sparking debate within the academic community regarding its advantages, risks, and potential impact on human capabilities. While countries such as the United States, China, and Turkey have institutional positions on the subject, in Mexico, discussion and regulation are still in early stages. The objective of this paper is to analyze the public policies and editorial guidelines on the use of IAGen in scientific journals published by leading Mexican institutions, with the aim of identifying how the scientific community participates, from the publisher’s perspective, in the regulation of this technology in the preparation and publication of research. The exploratory study was carried out through a documentary analysis of official government portals and a review of the editorial criteria for the use of GenAI in the journals of the educational institutions ranked among the top in the World University Rankings 2026. The results show that, under Mexican law, there are still no regulatory frameworks that regulate the use and application of GenAI. In the editorial field, 47% of journals have no specific guidelines, 9% prohibit their use, and 44% allow them under certain restrictions. Its potential as a support tool is recognized, though the author’s responsibility and the need to make its use transparent are emphasized. We agree that GenAI is a tool for researchers, not a substitute for their intellectual work.